2020
DOI: 10.1038/s41598-020-59945-w
|View full text |Cite
|
Sign up to set email alerts
|

Production, extraction and characterization of Chlorella vulgaris soluble polysaccharides and their applications in AgNPs biosynthesis and biostimulation of plant growth

Abstract: Chlorella vulgaris, like a wide range of other microalgae, are able to grow mixotrophically. this maximizes its growth and production of polysaccharides (pS). the extracted polysaccharides have a complex monosaccharide composition (fructose, maltose, lactose and glucose), sulphate (210.65 ± 10.5 mg g −1 PS), uronic acids (171.97 ± 5.7 mg g −1 pS), total protein content (32.99 ± 2.1 mg g −1 PS), and total carbohydrate (495.44 ± 8.4 mg g −1 pS). fourier transform infrared spectroscopy (ft-iR) analysis of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(57 citation statements)
references
References 106 publications
3
45
1
1
Order By: Relevance
“…The cell walls of microalgae are often destroyed to ensure access to proteins, amino acids, and other components. It has been reported that some microalgae contain soluble proteins in their cytoplasm [ 3 , 4 ]. In addition, microalgae with chloroplasts contain soluble protein, central pyrenoid, and phytobiliproteins, although some microalgae, such as Arthrospira platensis , instead, have thylakoid sacs surrounding the peripheral cytoplasm associated with phycobilisomes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cell walls of microalgae are often destroyed to ensure access to proteins, amino acids, and other components. It has been reported that some microalgae contain soluble proteins in their cytoplasm [ 3 , 4 ]. In addition, microalgae with chloroplasts contain soluble protein, central pyrenoid, and phytobiliproteins, although some microalgae, such as Arthrospira platensis , instead, have thylakoid sacs surrounding the peripheral cytoplasm associated with phycobilisomes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1 , more than 65% of the carbohydrate is dietary fiber, which appears to be derived from the Chlorella cell wall. Various polysaccharides have been extracted and characterized [ 22 , 23 , 24 , 25 ]. Chlorella polysaccharides exhibited a variety of biologically active compounds, including antioxidants [ 24 ] and stimulators of plant growth [ 25 ].…”
Section: Nutrients In Commercial Chlorella Prodmentioning
confidence: 99%
“…Various polysaccharides have been extracted and characterized [ 22 , 23 , 24 , 25 ]. Chlorella polysaccharides exhibited a variety of biologically active compounds, including antioxidants [ 24 ] and stimulators of plant growth [ 25 ]. Tabarsa et al [ 26 ] characterized an immune-enhancing water-soluble α-glucan prepared from C. vulgaris .…”
Section: Nutrients In Commercial Chlorella Prodmentioning
confidence: 99%
“…Microalgae cultivation is attracting more research due to its ability to synthesize various biologically active substances, the rapid growth of biomass, and the possibility of adjusting their biochemical composition depending on the cultivation conditions [ 1 , 2 , 3 ]. Unlike heterotrophic microorganisms, which require various organic compounds for growth, single-celled photosynthetic organisms produce biomass from fully oxidized inorganic substances and mineral elements due to light energy converted during photosynthesis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biologically active substances from microalgae can exhibit antioxidant, immunostimulating, antibacterial, antiviral, antitumor, antihypertensive, regenerative, and neuroprotective effects [ 6 , 7 , 8 ]. These compounds are required in medicine, cosmetology, food industry, fish farming, energy production, agriculture, feed, and functional food production [ 2 ].…”
Section: Introductionmentioning
confidence: 99%